Delayed Infiltration of Peripheral Monocyte Contributes to Phagocytosis and Transneuronal Degeneration in Chronic Stroke. Issue 7 (3rd June 2022) - Park, Keun Woo; Ju, Hyunwoo; Kim, Il-doo; Cave, John W.; Guo, Yang; Wang, Wei; Wu, Zhuhao; Cho, Sunghee
Abstract : Background: Mononuclear phagocytes, including monocyte-derived macrophages (MDMs) and microglia, contribute to infarct development as well as tissue repair in the postischemic brain. Here, we identify the origin and function of MDMs in the brain during poststroke repair processes. Methods: Adult mice were subjected to transient middle cerebral artery occlusion. Longitudinal brain atrophy and secondary degeneration were evaluated during acute to recovery phases of stroke. Adoptive transfer of GFP+ splenocytes into asplenic mice was used to distinguish MDMs from resident microglia. Fluorescence beads were injected into stroked animals to examine phagocytic function. Results: Progressive atrophy and neuronal degeneration in remote regions were observed in chronic stroke, which also was accompanied by MDM infiltration into the ipsilateral hemisphere. Compared with microglia, MDMs had significantly higher phagocytic activity. MDM trafficking and phagocytosis was spatiotemporally regulated with acute and prolonged infiltration into infarcted tissue, as well as delayed entry in remote areas such as the thalamus and substantia nigra. Conclusions: The stepwise and long-lasting involvement of MDMs at multiple poststroke stages shows that MDMs have a role in progressive stroke-induced injury and repair processes. These findings suggest that manipulating monocyte entry at different stroke stages may be an effective immune-based strategy to limit injury propagation in chronic stroke.